'Custom' and fractured 'community': mining, property disputes and law on the platinum belt, South Africa. Issue 2 (3rd March 2016) - Mnwana, Sonwabile
Abstract: Drawing on a recent study carried out in the Bakgatla-ba-Kgafela tribal authority area in South Africa's North West province, this article demonstrates that rural-based platinum mining generates intense struggles over 'communal' property – land and mining revenues. Competing versions of custom and contrasting group identities dominate these struggles. Since rights to communal property are secured through group membership and defined through custom, custom itself has become a space for contestation. It is the inflexibility in the way the state and the courts conceive custom – as a rigid set of rules – which perpetuates inequality and disputes at village level.